Devising a colorimetric aptasensor for detection of basal stem rot-associated RNA marker during early Ganoderma boninense infection in oil palm - Bahari, Mohammad Nazri Abdul; Abdullah, Siti Nor Akmar; Sakeh, Nurshafika Mohd; Ahmad, Khairulmazmi; Shaharuddin, Noor Azmi; Abu Seman, Idris; Osman, Rosiah (Elsevier, 2023)
Basal stem rot (BSR) is a detrimental disease in oil palm (Elaeis guineensis) due to the host's lack of symptoms during the early phase of infection. Early detection of BSR at non-symptomatic phase is feasible via molecular-based approaches and has become the major interest among researchers. Our previous study had identified a differentially expressed gene encoding auxin efflux carrier component 5-like (EgPIN5) at 11 day-post-inculation of Ganoderma boninense (symptomless early stage of infection) on oil palm seedlings. We further evaluated the gene expression on samples collected from an oil palm plantation at different BSR stages (symptomless, mild and severe). Our findings revealed that EgPIN5 was expressed in symptomless group but was not expressed in either mild or severe BSR groups. Next, we developed a sandwich-type aptamer-based lateral flow assay (LFA) against EgPIN5 RNA by adapting the versatile DNA-functionalized gold nanoparticles for colorimetric detection. The LFA strip demonstrated visible colorimetric signal of EgPIN5 RNA at 12.5 ng/μL with limit of detection at 2.45 ng/μL using a scanning device. Based on our consistent results, we presented EgPIN5 as a diagnostic biomarker for symptomless BSR infection in oil palm. Utilization of LFA assay strip for practical EgPIN5 RNA detection is hoped to encourage establishment of a fast, cheap, and sensitive point-of-care detection system in plant biology. © 2023 Elsevier Ltd